Do Collaborative Care Managers and Technology Enhance Primary Care Satisfaction with Care from Embedded Mental Health Providers? - Leung, Lucinda B. (J Gen Intern Med, 2020)
BACKGROUND: To improve mental health care access, the Veterans Health Administration (VA) implemented Primary Care-Mental Health Integration (PC-MHI) in clinics nationally. Primary care clinical leader satisfaction can inform model implementation and may be facilitated by collaborative care managers and technology supporting cross-specialty collaboration. OBJECTIVE: (1) To determine primary care clinical leaders’ overall satisfaction with care from embedded mental health providers for a range of conditions and (2) to examine the association between overall satisfaction and two program features (care managers, technology). DESIGN: Cross-sectional organizational survey in one VA region (Southern California, Arizona, and New Mexico), 2018. PARTICIPANTS: Sixty-nine physicians or other designated clinical leaders in each VA primary care clinic (94% response rate). MAIN MEASURES: We assessed primary care clinical leader satisfaction with embedded mental health care on four groups of conditions: target, non-target mental health, behavioral health, suicide risk management. They additionally responded about the availability of mental health care managers and the sufficiency of information technology (telemental health, e-consult, instant messaging). We examined relationships between satisfaction and the two program features using χ(2) tests and multivariable regressions. KEY RESULTS: Most primary care clinical leaders were “very satisfied” with care for targeted anxiety (71%) and depression (69%), but not for other common conditions (37% alcohol misuse, 19% pain). Care manager availability was significantly associated with “very satisfied” responses for depression (p = .02) and anxiety care by embedded mental health providers (p = .02). Highly rated sufficiency of communication technology (only 19%) was associated with “very satisfied” responses to suicide risk management (p = .002). CONCLUSIONS: Care from embedded mental health providers for depression and anxiety was highly satisfactory, which may guide improvement among less satisfactory conditions (alcohol misuse, pain). Observed associations between overall satisfaction and collaborative care features may inform clinics on how to optimize staffing and technology based on priority conditions. ELECTRONIC SUPPLEMENTARY MATERIAL: The online version of this article (10.1007/s11606-020-05660-1) contains supplementary material, which is available to authorized users.